The Impact of Service Innovation Culture on Employee Service Innovation Behavior and New Service Development: Evidence from North Cyprus Hotel Industry - Baradarani, Sarvnaz (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2018)
The aim of this study is to focus on the service innovation culture in the formation of employees’ service innovation behavior and new service development based on two fit theories. More specifically, the research evaluates and examines the mediating role of challenge-oriented citizenship behavior, charged behavior and knowledge sharing in the aforementioned relationship. To test the hypotheses, two-step structural equation modeling with bootstrapping estimation was conducted in AMOS, using data from four-hundred full-time hotel employees over a one-month time period. This thesis establishes that the development of a service innovation culture is positively related to the employee service innovation behavior and new service development. In addition, the results indicate that there is a partially mediating role for the challenge-oriented citizenship behavior, expanded charged behavior (encompassing vitality and creative self-efficacy) and knowledge sharing of employees in the relationship among service innovation culture with employee service innovation behavior and new service development. Findings of this thesis highlight the need for managers to incorporate a secure and trusting work environment so hotel employees will eagerly participate in the service innovation process by voicing their novel ideas, and communicating through sharing their knowledge. Managers can also consider the significance of the employee selection procedures and take advantage of employing university graduate for service jobs. Keywords: Service innovation culture, employee service innovation behavior, new service development, challenge-oriented citizenship behavior, charged behavior, knowledge sharing.

ÖZ: Bu çalışmanın amacı, otellerde çalışan personelin ilgili literatürde yer alan iki uyum teorisine bağlı olarak hizmet yeniliği davranışlarının ve yeni hizmet geliştirme anlayışlarının oluşumunda etkili olan hizmet yenilik kültürüne odaklanmaktır. Daha spesifik olarak, araştırmada, yukarıda bahsedilen ilişkide duygu yüklü davranış ile bilgi paylaşımı, meydan okuma odaklı vatandaşlık davranışının aracılık rolü incelenerek değerlendirilmiştir. Hipotezleri test etmek için, önyükleme tahminiyle iki aşamalı yapısal eşitlik modellemesi yöntemi ile dört yüz otel çalışanından bir aylık süre boyunca elde edilen verileri kullanarak AMOS'da gerçekleştirilmiştir. Çalışma, bir hizmet yenilik kültürünün geliştirilmesinin, çalışanların hizmet yeniliği davranışları ve yeni hizmet geliştirme ile olumlu bir ilişki kurduğunu ortaya koymaktadır. Buna ek olarak, sonuçlar, meydan okuma odaklı vatandaşlık davranışının, geliştirilmiş duygu yüklü davranışın (canlılığı içeren ve yaratıcı öz yeterlik kapsamına giren) ve hizmet yeniliği kültürü ile çalışanların hizmet yeniliği davranışları arasındaki ilişkide bilgi paylaşımının kısmen aracılık ettiği bir role ve yeni hizmet geliştirmeye işaret etmektedir. Tezin bulguları, yöneticilerin güvenli ve inanılır bir çalışma ortamı oluşturmalarına olan ihtiyacı vurgulamakta olup, böylece otel çalışanları, yeni fikirlerini dile getirerek ve bilgilerini paylaşarak iletişim kurarak hizmet yeniliği sürecine istekli bir şekilde katıldıkları sonucunu ortaya koymaktadır. Yöneticiler, ayrıca, çalışan seçimi prosedürünün önemini de değerlendirerek hizmet ile ilgili pozisyonlar için üniversite mezunlarından faydalanabilecektir. Anahtar kelimeler: Hizmet yeniliği kültürü, çalışanların hizmet yeniliği davranışı, yeni hizmet geliştirme, meydan okuma odaklı yurttaşlık davranışı, ücret davranışları, bilgi paylaşımı.
Doctor of Philosophy in Tourism Management. Thesis (Ph.D.)--Eastern Mediterranean University, Faculty of Tourism, 2018. Supervisor: Prof. Dr. Hasan Kılıç.
Keywords: Tourism; Service Innovation Culture--Employee Service Innovation Behavior--Hotel Industyr--Tourism--Cyprus (Turkish Republic of Northern Cyprus, 1983-); Service innovation culture; employee service innovation behavior; new service development; challenge-oriented citizenship behavior; charged behavior; knowledge sharing